Characterization of Silver Nanowire Layers in the Terahertz Frequency Range - Przewłoka, Aleksandra; Smirnov, Serguei; Nefedova, Irina; Krajewska, Aleksandra; Nefedov, Igor S.; Demchenko, Petr S.; Zykov, Dmitry V.; Chebotarev, Valentin S.; But, Dmytro B.; Stelmaszczyk, Kamil; Dub, Maksym; Zasada, Dariusz; et al. (Royal Institute of Technology, 2021)
Transmittance of thin layers of silver nanowires with increasing densities.

Nanowire dimensions of Samples:
- A: 40 ± 5 nm diameter, 35 ± 5 µm length
- B: 35 ± 5 nm diameter, 25 ± 5 µm length
- C: 30 ± 5 nm diameter, 20 ± 3 µm length

CSV files with the frequency in THz in the first column and the transmittance in the second column.

The dataset was originally published in DiVA and moved to SND in 2024.

Transmission av tunna lager av silver nanotrådar med ökande densiteter.

Nanotråddimensioner för prover:
- A: 40 ± 5 nm diameter, 35 ± 5 µm längd
- B: 35 ± 5 nm diameter, 25 ± 5 µm längd
- C: 30 ± 5 nm diameter, 20 ± 3 µm längd

CSV-filer med frekvensen i THz i den första kolumnen och transmittansen i den andra kolumnen.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Characterization of Silver Nanowire Layers in the Terahertz Frequency Range
Keywords: nanotechnology; nanoteknik; Nano-technology; Nanoteknik